Cost-effectiveness of abatacept compared to other biological agents for the treatment of moderately to severely active rheumatoid arthritis in patients who failed with methotrexate in Peruvian Social Security during 2010 - Becerra Rojas, Felipe (2024)
Objective: To estimate the cost-effectiveness of Abatacept in combination with Methotrexate (MTX) versus other biologic DMARDs in combination with MTX in patients with moderately to severely active rheumatoid arthritis. Materials and methods: A sequential therapy model was adapted for representing disability using the HAQ Index in a 5-year horizon period for a 1000-patient cohort. Abatacept in combination with MTX was compared against etanercept, rituximab, infliximab, adalimumab, and tocilizumab, all of them combined with MTX. Results: The cost of abatacept therapy was S/. 169 263 and its effectiveness was found to be 1.96 QALY. Compared to etanercept, adalimumab, infliximab and tocilizumab, abatacept has shown to be the most effective agent in terms of QALYs and the least expensive. Compared to rituximab, abatacept has an incremental cost effectiveness ratio of S/. 75 493 per QALY gained. Conclusions: According to this model, abatacept was found to be superior compared to etanercept, adalimumab, infliximab, and tocilizumab, from the Peruvian Social Security (EsSalud) perspective for the treatment of moderately to severely active Rheumatoid Arthritis in patients who failed using a MTX-based therapy.